Do Fluctuations in Energy Sector Matter for Monetary Policy? An ARDL and NARDL Approach - Yermekova, Zhanna; Coban, Orhan; Turarov, Dauren; Askarova, Zhanar; Aliyeva, Baglan (International Journal of Energy Economics and Policy, 2026)
The relationship between monetary policy and the energy industry in the Republic of Kazakhstan was examined using statistical indicators from the official website of the World Bank spanning 29 years (1994–2022). The following variables were used: Domestic credit to private sector by banks, Official exchange rate, Inflation, Alternative and nuclear energy, Combustible renewables and waste, Electric power consumption, Renewable energy consumption, Fossil fuel energy consumption, Electricity production from coal sources, Energy use, Electricity production from oil sources, and Foreign direct investment. In the estimation, Autoregressive Distributed Lag and Non-Linear Autoregressive Distributed Lag models were applied and appropriate tests were conducted. The models yielded findings indicating a number of interrelations between the variables. As observed, monetary policy is closely linked to the energy industry, if not connected directly. Namely, it was found that a number of energy indicators affect inflation. We hope these levers can be used to shape the nation’s inflation policy. This study and findings will be useful for other academics, as there is a lack of research in this area.